TEACHING DIFFICULT HISTORY IN THE DEEP SOUTH OF THAILAND: HOW TEACHERS APPLY JUSTICE-SENSITIVE PEDAGOGY INTO THE CLASSROOMS - Daengkomane , Pattawee; Hsiao-Lan Chen (Journal of Educational Review Faculty of Education in MCU, 2026)
The purpose of this study is: 1) to examine how teachers conceptualize Justice-sensitive Pedagogy (JSP); 2) to explore how teachers apply JSP in teaching difficult history topics; and 3) to investigate the institutional, political, and pedagogical constraints affecting the implementation of JSP in the deep south provinces of Thailand. A qualitative case study approach was used to study six secondary school teachers from six schools with diverse educational contexts. In addition, interviews were conducted with two university educators and two education policymakers. Data were collected through semi-structured interviews and analyzed using thematic analysis. The results show that teachers viewed JSP not as a completely new teaching method, but rather as an approach they had already applied indirectly in classroom practice. This indirect teaching strategy was influenced by the national curriculum, which does not explicitly include difficult history content, resulting in teaching practices that depended largely on individual teachers’ choices and interpretations. The findings also indicate that ongoing violence in the three southern provinces, as well as differences between public schools and private Islamic schools, affected the design of teaching and learning activities. Institutional limitations, political sensitivities, and pedagogical challenges were found to constrain the implementation of JSP in schools. This study argues that the effectiveness of JSP cannot rely solely on the individual abilities of teachers, but requires systematic support through teacher training, curriculum development, learning materials, and educational policies. This study provides practical insights and theoretical support for the development of history education and peace-oriented pedagogy in conflict-affected contexts.